Human Ectoparasites Are Highly Prevalent in the Rural Communities of Northwest Ethiopia: A Community-Based Cross-Sectional Study. (July 2021) - Gizaw, Zemichael; Engdaw, Garedew Tadege; Nigusie, Adane; Gebrehiwot, Mulat; Destaw, Bikes
Background: Ectoparasites are organisms which inhabit the skin or outgrowths of the skin of another organism (the host). Many ectoparasites are known to be vectors of pathogens, which the parasites typically transmit to hosts. Though, ectoparasites are common in the vulnerable groups and economically disadvantaged communities, there is limited evidence on its magnitude in Ethiopia. This community-based cross-sectional study was, therefore, conducted to assess the prevalence and associated factors of ectoparasites in the rural communities of northwest Ethiopia. Methods: A community-based cross-sectional study design with structured observation was conducted among 1191 randomly selected rural households in northwest Ethiopia in May 2016. Data were collected using structured interviewer administered interview questionnaire and structured observation checklist. Prevalence of human ectoparasites in the rural communities was defined as the presence of one or more lice, fleas, bed bugs, mites, and ticks and the presence of these ectoparasites were observed by trained environmental health experts. Multivariable binary logistic regression analysis was used to identify variables associated with prevalence of ectoparasites on the basis of adjusted odds ratio (AOR) with 95% confidence interval (CI) and P values <.05. Results: Of a total of 1191 rural households, human or hair lice were observed in one or more of the family members in 186 (15.6%) rural households. Similarly, fleas were observed in more than half, 609 (51.1%) of rural households and bed bugs were observed in 441 (37%) rural households. Furthermore, mites and ticks were reported in 113 (9.5%) and 130 (10.9%) of the households respectively. Accordingly, one or more ectoparasites were observed in 865 of 1191 rural households. The presence of one or more ectoparasites was, therefore, found to be 72.6% (95% CI = 70%-75.1%). The prevalence of ectoparasites was statistically associated with educational status of the female head being not educated (AOR = 1.476, 95% CI = 1.001, 2.177) and absence close supervision by health extension workers (AOR = 2.151, 95% CI = 1.205, 3.843). Conclusion: The prevalence of one or more ectoparasites was high in the rural communities of northwest Ethiopia. The high prevalence was associated with education status of the female head and close supervision of households by health extension workers. Disseminating health information about intervention strategies of ectoparasites and closely supervising the rural households need to be considered.